Implementation of System Environment for Smart Authentication Service - Min, Young-Gee; Kim, Bong-Hyun; Kim, Eon-Gon (International Journal of Engineering and Technology, 2026)
Background/Objectives: As the various security threats increase, security accidents are frequent due to leakage of ID and password and illegal stealing. As a result, various cyber crimes and property damages are occurring due to the leakage of personal information online.Methods/Statistical analysis: Security technologies are continuously being developed to protect information by blocking illegal activities such as accessing, browsing, copying, stealing or destruction of certain information by unauthorized persons. The use of existing web services is usually a method of using the ID / password method or the mobile phone authentication number by using a mobile phone or the like. These existing methods are limited in terms of operation, time, inconvenience in use, and functional limitations.Findings: Therefore, in this paper, we set the access control time and restrict the re-login of the web server with the same ID and password for the access control time, so that after a third party who illegally logs in to the web server is forcibly logged out from the web server, Prevents re-login with username and password, re-login to the web server, arbitrarily changing the user ID and password to prevent the user from legitimately logging in to the web server. Also, through the setting control time, the user can re-issue the password to the web server operator by requesting the web server to secure time for logging in to the web server.Improvements/Applications: In this paper, we have implemented a system environment to provide smart authentication service. Through this, we developed an Android-based smartphone app client that can be installed on the smartphone and perform subscription, configuration, and various functions, and implemented a smart certification service environment that performs various information and statistics management.
Keywords: Smart Authentication; Authentication Management Server; Push Server; Web Access Notification; PC Client.